1983
DOI: 10.1172/jci111123
|View full text |Cite
|
Sign up to set email alerts
|

Identification and structural characterization of two incompletely processed forms of the fourth component of human complement.

Abstract: A B S T R A C T Immunoprecipitates of human C4 fromEDTA-plasma were incubated with [14C]methylamine and analyzed by sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis and fluorography. In addition to finding label in the a-chains of the secreted (C45) and predominant plasma (C4P) forms of C4, two additional molecules with apparent molecular weights of -168,000 (p168) and '125,000 (p125) covalently incorporated methylamine, indicating the presence of an internal thioester bond. These two molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…90, 70 and ^0 kD, corresponding to pro-C4 [361 and C4 i:, {i and y chains, were identified in the GMC culture supernatant (F^ig, 2a). The band of ^^ 160 kD precipitated by anli-C4 probably represents an s fi intermediate of C4 [36], The eKtraeellular C4 ot. (i and y chains were more strongly detected in IF^N-y-trealed cells compared with untreaied control eells (Fig, 2a), Kinetic studies indicated ihat there wa^ an initial increase ir.…”
Section: Biosynthesis Of C3 and C4 Proteins By Gmcmentioning
confidence: 98%
“…90, 70 and ^0 kD, corresponding to pro-C4 [361 and C4 i:, {i and y chains, were identified in the GMC culture supernatant (F^ig, 2a). The band of ^^ 160 kD precipitated by anli-C4 probably represents an s fi intermediate of C4 [36], The eKtraeellular C4 ot. (i and y chains were more strongly detected in IF^N-y-trealed cells compared with untreaied control eells (Fig, 2a), Kinetic studies indicated ihat there wa^ an initial increase ir.…”
Section: Biosynthesis Of C3 and C4 Proteins By Gmcmentioning
confidence: 98%
“…Trypsin Digestion, Radiolabelling with ,4C Methylamine and Fluorography C4 protein, immunoprecipitated from bovine plasma, was reacted with l4C methylamine hydro chloride as described by Chan and Atkinson [17]. This protein was then subjected to SDS-PAGE, or first partially digested with trypsin and then electrophoresed.…”
Section: Polyacrylamide Get Electrophoresismentioning
confidence: 99%
“…3). Radiolabeled C4 a and A chains and an a-/3 intermediate (27) were detected in the extracellular fluid of IFN-y-activated monocytes. The C4 y chain was also detected in other experiments (data not shown).…”
Section: Resultsmentioning
confidence: 99%